Analysis of congenital hearing loss after neonatal hearing screening - Verstappen, Gill; Foulon, Ina; Van den Houte, Kelsey; Heuninck, Emilie; Van Overmeire, Bart; Gordts, Frans; Topsakal, Vedat (Frontiers in Pediatrics, 2023)
Introduction: Neonates undergo neonatal hearing screening to detect congenital hearing loss at an early stage. Once confirmed, it is necessary to perform an etiological workup to start appropriate treatment. The study objective was to assess the different etiologies, risk factors, and hearing results of infants with permanent hearing loss and to evaluate the efficacy and consequences of the different screening devices over the last 21 years. Methods: We conducted a single-center retrospective cohort analysis for all neonatal hearing screening program referrals and performed an etiological workup in case of confirmed hearing loss. We analyzed the evolution of the etiological protocols based on these results. Results: The governmental neonatal hearing screening program referred 545 infants to our center. Hearing loss was confirmed in 362 (66.4%) infants and an audiological workup was performed in 458 (84%) cases. 133 (24.4%) infants were diagnosed with permanent hearing loss. Ninety infants (56 bilateral and 34 unilateral) had sensorineural hearing loss, and the degree was predominantly moderate or profound. The most common etiology in bilateral sensorineural hearing loss was a genetic etiology (32.1%), and in unilateral sensorineural hearing loss, an anatomical abnormality (26.5%). Familial history of hearing loss was the most frequently encountered risk factor. Conclusion: There is a significant number of false positives after the neonatal hearing screening. Permanent hearing loss is found only in a limited number of infants. During the 21 years of this study, we noticed an increase in etiological diagnoses, especially genetic causes, due to more advanced techniques. Genetic causes and anatomical abnormalities are the most common etiology of bilateral and unilateral sensorineural hearing loss, respectively, but a portion remains unknown after extensive examinations.